Engineering optimization : theory and practice - Rao, Singiresu S. , 1944- (John Wiley & Sons, 2009)
This is the only book on the market that discusses all the important methods of optimization. All the methods are presented in a simple language in the most comprehensive manner. Nonlinear, linear, geometric, dynamic and stochastic programming techniques are presented with a focus on engineering applications